Endoscopic Full-Thickness Resection Combined with Laparoscopic Surgery - Chan Gyoo Kim (Korean Society of Gastrointestinal Endoscopy, 2018)
Endoscopic full-thickness resection combined with laparoscopic surgery was recently developed. These procedures could be categorized as "Cut first and then suture" and "Suture first and then cut". "Cut first and then suture" includes laparoscopic and endoscopic cooperative surgery (LECS) and laparoscopy-assisted endoscopic full-thickness resection (LAEFR). Recent studies have demonstrated the safety and efficacy of LECS and LAEFR. However, these techniques are limited by the related exposure of the tumor and gastric mucosa to the peritoneal cavity and manipulation of these organs, which could lead to viable cancer cell seeding and the spillage of gastric juice into the peritoneal cavity. In the "Suture first and then cut" technique, the serosal side of the stomach is sutured to invert the stomach and subsequently endoscopic resection is performed. In this article, details of these techniques, including their advantages and limitations, are described.